(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The Article was dedicated to convey narrative style of “through the tunnel” story. Third-person narration is used in "Through the Tunnel" by Doris Lessing. The narrator, who is not involved in the story’s storyline, describes the events from a variety of characters’ points of view. Apart from that I decribed about language and characters of the story